Web-based Monitoring System for Power Electronics Devices on Off-grid Solar Power Generator - Amirul Luthfi; Eka Putra Waldi; Darmawan Darmawan; Baharudin Baharudin; Budi Sunaryo (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
Power electronic devices are the main component of the solar power generation system. This study proposes a web-based monitoring system which presents power electronic performance parameter in a real-time across an internet connection. The investigation takes ACS712 and PZEM-004T for the power converter performance measuring and Arduino Mega 2560 with an ethernet shield for data acquisition and transmission. This paper describes the schematic design of the hardware and also explains the software work-flow and structure. The test and calibration on the sensor's voltage and current to standard digital multi-meter Tektronix DMM4050 show the sensor able to accurately read the converter performance parameter and meet the standard IEC-61724. The functionality test on the web-based information system indicates the designed user interface to present the power electronic performance parameter of the solar power generator.Keywords: Monitoring System, Power Electronics and Solar Power